KORELASI ASPEK LINGKUNGAN TERHADAP KEJADIAN ISPA PADA BALITA - Iswati, Ning; Lestari, Dwi; Sohilauw, Damayanti Sima Sima; Abdullah, Asmiwarti (Ensiklopedia of Journal, 2025)
Abstract: Acute Respiratory Infection (ARI) is one type of infectious disease that spreads rapidly through the process of transmission from one individual to another. Purwosari Health Center is a health center with cases of ARI in children under five years old. The purpose of the study was to determine the correlation of environmental aspects to the incidence of ARI in toddlers. The research design used in this study was cross sectional. The research was conducted in the working area of Purwosari Health Center. The study was conducted from May to July 2024. The study population was all toddlers in the Purwosari Health Center Working Area of Bojonegoro Regency as many as 150 toddlers. The sample amounted to 35 toddlers. The sampling technique used in this study was Simple random sampling. Data analysis was done univariate and bivariate. The results showed a relationship between home ventilation (p value: 0.04) and home humidity (p value: 0.038) with the incidence of ARI in children under five. It is recommended to the community to take various measures to prevent the incidence of ARI in toddlers such as applying healthy living behavior by providing food with balanced nutrition with the child's daily menu such as vegetables, meat, fruits.Keywords: Toddlers, ARI, Home Ventilation